Lead-free glass powder and preparation method and application thereof

By using boron oxide, silicon oxide, aluminum oxide, zinc oxide, calcium oxide and alkali metal oxide in lead-free glass powder and modifying zinc oxide with Ti3C2Tx nanosheets, the thermal expansion characteristics and chemical stability of lead-free glass powder are solved. The problem of the problem of the quality of lead-free glass powder with low expansion coefficient and high mechanical strength is achieved, which is suitable for semiconductor materials.

CN118771733BActive Publication Date: 2024-12-24RIHONG SEMICONUCTING MATERIAL NANTONG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411244307.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-24
Estimated Expiration
2044-09-06

AI Technical Summary

Technical Problem

The existing lead-free glass powder has defects such as toxic and harmful substances, poor thermal expansion characteristics, chemical stability, and easy crystallization in large-scale industrial production, which is difficult to promote and apply.

Method used

Boron oxide, silicon oxide, aluminum oxide, zinc oxide, calcium oxide and alkali metal oxide are used to cooperate with each other, and zinc oxide is coated and modified by Ti3C2Tx nanosheets to prepare lead-free with low expansion coefficient and excellent chemical stability. Glass powder.

Benefits of technology

It realizes the low melting temperature, low expansion coefficient and good mechanical strength of lead-free glass powder, and replaces the existing lead-containing glass powder and is suitable for semiconductor materials.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a lead-free glass powder and a preparation method and application thereof, and relates to the technical field of materials. The lead-free glass powder comprises the following components by weight: 40-55 parts of boron oxide; 2-18 parts of silicon dioxide; 4-16 parts of aluminum oxide; 5-10 parts of modified zinc oxide; 6-10 parts of calcium oxide; 3-6 parts of alkali metal oxide; the D50 particle size of the modified zinc oxide is 20-50 nm; the modified zinc oxide is composed of Ti 3 C 2 T x The nanosheets are obtained by coating and modifying zinc oxide. The lead-free glass powder prepared by the invention has a lower expansion coefficient and excellent chemical stability and mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of materials, and in particular to a lead-free glass powder and a preparation method and application thereof. Background Art

[0002] Lead-free low-melting-point glass powder has lower melting temperature and sealing temperature, good heat resistance and chemical stability, and high mechanical strength. In the semiconductor field, lead-free glass powder is one of the indispensable materials in the semiconductor manufacturing process. It not only protects chips and circuits, but also improves the performance and stability of components. At the same time, with the improvement of environmental protection requirements, the use of lead-free glass powder is also required to comply with environmental protection requirements.

[0003] However, the current lead-free glass powder contains toxic and harmful substances, has poor thermal expansion characteristics and chemical stability, and is easy to crystallize, which makes it difficult to promote and apply in large-scale industrial production. Therefore, there is room for improvement. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a lead-free glass powder and a preparation method and application thereof. The lead-free glass powder prepared by the present invention has a lower expansion coefficient and excellent chemical stability and mechanical strength.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] In a first aspect, the present invention provides a lead-free glass powder, comprising the following components in parts by weight:

[0007] 40-55 parts of boron oxide; 2-18 parts of silicon dioxide; 4-16 parts of aluminum oxide; 5-10 parts of modified zinc oxide; 6-10 parts of calcium oxide; 3-6 parts of alkali metal oxide; the D50 particle size of the modified zinc oxide is 20-50 nm; the modified zinc oxide is Ti3C2T x Obtained by coating and modifying zinc oxide with nanosheets.

[0008] In the present invention, boron oxide is the main glass former in the glass and exists in a layered structure in the glass. The addition of boron can reduce the softening temperature and expansion coefficient, and stabilize the chemical properties of the glass. The addition of silicon dioxide and aluminum oxide can reduce the crystallization tendency of the glass, while improving the chemical stability of the glass, and can adjust the linear expansion coefficient of the glass. The addition of zinc oxide can increase the chemical stability of the glass and reduce the expansion coefficient of the glass. Calcium oxide is a divalent network exometallic oxide, and its main function in the glass is a stabilizer, which increases the chemical stability and mechanical strength of the glass. Alkali metal oxides can reduce the melting temperature of the glass and can also reduce the viscosity of the glass liquid. Therefore, the present invention adopts boron oxide, silicon dioxide, aluminum oxide, zinc oxide, calcium oxide, and alkali metal oxides to cooperate with each other, which can not only reduce the melting temperature and expansion coefficient of the glass, but also make the glass powder have excellent chemical stability.

[0009] Ti3C2T x Nanosheets are a two-dimensional sheet-like nanomaterial with rich surface functional groups, good flexibility, large specific surface area and excellent mechanical properties. x The coating and modification of zinc oxide by nanosheets not only makes the various components in the glass powder evenly dispersed, thereby improving the stability of the glass powder; it is also beneficial to improve the flexibility of the glass powder and further improve the mechanical strength of the glass powder.

[0010] The present invention adopts modified zinc oxide in a specific particle size range, which can better provide the chemical stability of the glass while further reducing the expansion coefficient of the glass, promoting the glass powder system to have good mechanical strength and thermal shock resistance, and enhancing the flexural strength of the glass powder.

[0011] Preferably, the alkali metal oxide is at least one of sodium oxide, lithium oxide and potassium oxide.

[0012] Preferably, the alkali metal oxide is a mixture of sodium oxide and potassium oxide, and the mass ratio of the sodium oxide to potassium oxide is (3-5):1.

[0013] The present invention adopts a specific ratio of sodium oxide and potassium oxide to compound, which can reduce the viscosity of glass powder in a molten state, make the components mix evenly, and is conducive to forming a stable glass composition with a dense microcrystalline structure, thereby reducing the sintering temperature of the glass powder.

[0014] Preferably, the mass ratio of sodium oxide to potassium oxide is in the range of any one or both of 3:1, 4:1, and 5:1.

[0015] Preferably, the method for preparing the modified zinc oxide comprises the following steps:

[0016] First, zinc oxide powder is prepared into a zinc oxide solution with a mass concentration of 3-6%, and then added into the Ti3C2Tx nanosheets and mixed evenly, and then the modified zinc oxide is prepared after drying.

[0017] Preferably, the lead-free glass powder comprises the following components in parts by mass:

[0018] 45-55 parts of boron oxide; 12-18 parts of silicon dioxide; 14-16 parts of aluminum oxide; 5-10 parts of modified zinc oxide; 6-10 parts of calcium oxide; 3-6 parts of alkali metal oxide.

[0019] Preferably, the mass percentage of the boron oxide in the lead-free glass powder is not less than 45%.

[0020] Preferably, the oil absorption of the glass powder is 15-20 g / 100g.

[0021] In a second aspect, the present invention further provides a method for preparing lead-free glass powder, comprising the following steps:

[0022] (1) Mix all components evenly to obtain a mixture;

[0023] (2) The mixture is then heated and kept warm to obtain glass liquid, and the glass liquid is then poured into cold water for quenching to obtain glass particles;

[0024] (3) Finally, the glass particles are ground into glass powder.

[0025] Preferably, in step (2), the temperature of the mixed material when heated is 700-850° C., and the insulation time is 1-2 h.

[0026] In a third aspect, the present invention also provides an application of lead-free glass powder in semiconductors.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The lead-free glass powder prepared by the present invention has a lower sintering temperature and good flexural strength, has good chemical stability and excellent mechanical properties when applied to semiconductor materials, and can replace existing lead-containing glass powder. DETAILED DESCRIPTION

[0029] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments, but the protection scope and implementation methods of the present invention are not limited thereto.

[0030] Unless otherwise specified, the materials and reagents used in the following examples are reagents and materials that can be obtained from commercial sources. Unless otherwise specified, the components and raw materials used in the examples and comparative examples of the present invention are all commercially available raw materials.

[0031] Ti3C2T x The nanosheets come from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.

[0032] The purity of the boron oxide, silicon dioxide, aluminum oxide, zinc oxide, calcium oxide and alkali metal oxide described in the present invention is greater than 99%.

[0033] Preparation Example

[0034] The preparation method of modified zinc oxide comprises the following steps:

[0035] First, zinc oxide powder was prepared into a zinc oxide solution with a mass concentration of 5.8%, and then Ti3C2T x The nanosheets were mixed evenly and dried at 100°C to obtain modified zinc oxide powder. The zinc oxide powder and Ti3C2T x The mass ratio of the nanosheets is 1:2. Example 1

[0036] A lead-free glass powder, comprising the following components in parts by weight:

[0037] 45 parts of boron oxide; 12 parts of silicon dioxide; 14 parts of aluminum oxide; 8 parts of modified zinc oxide; 6 parts of calcium oxide; 4 parts of sodium oxide; the D50 particle size of the modified zinc oxide is 20 nm.

[0038] A method for preparing lead-free glass powder comprises the following steps:

[0039] (1) Mix boron oxide, silicon dioxide, aluminum oxide, modified zinc oxide, calcium oxide and sodium oxide in a uniform ratio to obtain a mixture;

[0040] (2) The mixture is then heated at 700°C and kept at this temperature for 2 hours to obtain glass liquid, which is then poured into cold water for quenching to obtain glass particles;

[0041] (3) Finally, the glass particles are ground to obtain glass powder with an average particle size of 5 μm. Example 2

[0042] A lead-free glass powder, comprising the following components in parts by weight:

[0043] 45 parts of boron oxide; 12 parts of silicon dioxide; 14 parts of aluminum oxide; 8 parts of modified zinc oxide; 6 parts of calcium oxide; 4 parts of sodium oxide; the D50 particle size of the modified zinc oxide is 30 nm.

[0044] A method for preparing lead-free glass powder comprises the following steps:

[0045] (1) Mix boron oxide, silicon dioxide, aluminum oxide, modified zinc oxide, calcium oxide and sodium oxide in a uniform ratio to obtain a mixture;

[0046] (2) The mixture is then heated at 850°C and kept warm for 1 hour to obtain glass liquid, which is then poured into cold water for quenching to obtain glass particles;

[0047] (3) Finally, the glass particles are ground to obtain glass powder with an average particle size of 5 μm. Example 3

[0048] The difference from Example 1 is that the D50 particle size of the modified zinc oxide is 50 nm, and the other components and steps are the same as those in Example 1. Example 4

[0049] A lead-free glass powder, comprising the following components in parts by weight:

[0050] 45 parts of boron oxide; 12 parts of silicon dioxide; 14 parts of aluminum oxide; 8 parts of modified zinc oxide; 6 parts of calcium oxide; 4 parts of potassium oxide; the D50 particle size of the modified zinc oxide is 30 nm.

[0051] The difference between Example 4 and Example 2 is that the alkali metal oxide is potassium oxide. Example 5

[0052] A lead-free glass powder, comprising the following components in parts by weight:

[0053] 45 parts of boron oxide; 12 parts of silicon dioxide; 14 parts of aluminum oxide; 8 parts of modified zinc oxide; 6 parts of calcium oxide; 2 parts of sodium oxide; 2 parts of potassium oxide; the D50 particle size of the zinc oxide is 30 nm.

[0054] The difference between Example 5 and Example 2 is that the alkali metal oxide includes sodium oxide and potassium oxide, and the mass ratio of sodium oxide to potassium oxide is 1:1. Example 6

[0055] The difference from Example 4 is that the alkali metal oxide includes sodium oxide and potassium oxide, and the mass ratio of sodium oxide to potassium oxide is 3:1. The other components and steps are the same as those in Example 1. Example 7

[0056] The difference from Example 4 is that the alkali metal oxide includes sodium oxide and potassium oxide, and the mass ratio of sodium oxide to potassium oxide is 5:1. The other components and steps are the same as those in Example 1. Example 8

[0057] The difference from Example 4 is that the alkali metal oxide includes sodium oxide and potassium oxide, and the mass ratio of sodium oxide to potassium oxide is 7:1. The other components and steps are the same as those in Example 1. Example 9

[0058] A lead-free glass powder, comprising the following components in parts by weight:

[0059] 40 parts of boron oxide; 18 parts of silicon dioxide; 4 parts of aluminum oxide; 5 parts of modified zinc oxide; 10 parts of calcium oxide; 3 parts of sodium oxide; the D50 particle size of the zinc oxide is 30 nm. Example 10

[0060] A lead-free glass powder, comprising the following components in parts by weight:

[0061] 55 parts of boron oxide; 2 parts of silicon dioxide; 16 parts of aluminum oxide; 10 parts of modified zinc oxide; 6 parts of calcium oxide; 6 parts of sodium oxide; the D50 particle size of the zinc oxide is 30 nm.

[0062] Comparative Example 1

[0063] The difference from Example 2 is that silicon dioxide is not added to the lead-free glass powder, and the other components and steps are the same as those in Example 2.

[0064] Comparative Example 2

[0065] The difference from Example 2 is that no aluminum oxide is added to the lead-free glass powder, and the other components and steps are the same as those in Example 2.

[0066] Comparative Example 3

[0067] The difference from Example 2 is that calcium oxide is not added to the lead-free glass powder, and the other components and steps are the same as those in Example 2.

[0068] Comparative Example 4

[0069] The difference from Example 2 is that modified zinc oxide is not added to the lead-free glass powder, and the other components and steps are the same as those in Example 2.

[0070] Comparative Example 5

[0071] The difference from Example 2 is that no alkali metal oxide is added to the lead-free glass powder, and the other components and steps are the same as those in Example 2.

[0072] Comparative Example 6

[0073] The difference from Example 2 is that the D50 particle size of the modified zinc oxide is 10 nm, and the other components and steps are the same as those in Example 2.

[0074] Comparative Example 7

[0075] The difference from Example 2 is that the D50 particle size of the modified zinc oxide is 80 nm, and the other components and steps are the same as those in Example 2.

[0076] Comparative Example 8

[0077] The difference from Example 2 is that calcium oxide is replaced by magnesium oxide of equal mass, and other components and steps are the same as those in Example 2.

[0078] Comparative Example 9

[0079] The difference from Example 2 is that bismuth oxide of equal mass is used to replace boron oxide, and other components and steps are the same as those in Example 2.

[0080] Comparative Example 10

[0081] The difference from Example 2 is that the modified zinc oxide is replaced by zinc oxide of equal mass, and the other components and steps are the same as those in Example 2.

[0082] experiment

[0083] In order to verify the present invention, the products prepared in each embodiment and comparative example were subjected to the following performance tests, and the specific steps are as follows:

[0084] 1. Determination of thermal expansion coefficient: Pour the glass liquid in the above embodiment and comparative example into a stainless steel mold box and anneal; take the annealed flux and process it into a cylindrical glass with a length of 15 mm and a diameter of 3 mm. The above glass is selected as a standard sample, a load of 10 g is applied, and a TD5010SA-N thermal expansion meter produced by Bruker AXS Co., Ltd. is used to measure the thermal expansion coefficient of the lead-free glass powder prepared by the present invention.

[0085] 2. Determination of water resistance: The water resistance of the lead-free glass powder prepared by the present invention is determined according to GB / T 17129-1997; the grade classification is as follows:

[0086] A (glass leaching percentage is less than 0.04%); B (glass leaching percentage is 0.04-0.1%); C (glass leaching percentage is greater than 0.1-0.25%); D (glass leaching percentage is greater than 0.25-0.6%); E (glass leaching percentage is greater than 0.6-1.1%); F (glass leaching percentage is greater than 1.1%).

[0087] 3. Determination of acid resistance: The acid resistance of the lead-free glass powder prepared by the present invention is determined according to GB / T 17129-1997; the grade classification is as follows:

[0088] A (glass leaching percentage is less than 0.2%); B (glass leaching percentage is 0.2-0.35%); C (glass leaching percentage is greater than 0.35-0.65%); D (glass leaching percentage is greater than 0.65-1.2%); E (glass leaching percentage is greater than 1.2-2.2%); F (glass leaching percentage is greater than 2.2%).

[0089] 4. Determination of flexural strength: The flexural strength of the above-mentioned glass was measured with reference to JIS R 3111-3:2022.

[0090] The above experimental results are shown in Table 1 and Table 2.

[0091] Table 1

[0092] Test items Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 Example 9 Example 10 <![CDATA[Coefficient of expansion / 10 -7 / °C]]> 56 54 59 55 51 49 47 52 57 56 Water resistance A A A A A A A A A A Acid resistance B B B B A A A A B B Flexural strength / MPa 74 77 75 69 79 83 85 81 76 72

[0093] Table 2

[0094] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Comparative Example 8 Comparative Example 9 Comparative Example 10 <![CDATA[Coefficient of expansion / 10 -7 / °C]]> 77 65 58 62 60 69 72 74 60 69 Water resistance B B B B B B B B B B Acid resistance B B B B C C C B B C Flexural strength / MPa 54 56 45 57 59 52 56 51 59 62

[0095] According to Table 2, Comparative Examples 1-5 are compared with Example 2. No silicon dioxide is added in Comparative Example 1, no aluminum oxide is added in Comparative Example 2, no calcium oxide is added in Comparative Example 3, no zinc oxide is added in Comparative Example 4, and no alkali metal oxide is added in Comparative Example 5. The expansion coefficients of the glass powders in Comparative Examples 1-5 are all higher than those in Example 2, and the flexural strengths of the glass powders are all lower than those in Example 2. In addition, the water resistance of the glass powders in Comparative Examples 1-5 is not as good as that in Example 2, indicating that the lack of any of silicon dioxide, aluminum oxide, zinc oxide, calcium oxide, and alkali metal oxides cannot make the glass powder have good chemical stability. Therefore, the present invention can only reduce the expansion coefficient of glass by using boron oxide, silicon dioxide, aluminum oxide, zinc oxide, calcium oxide, and alkali metal oxides in a specific ratio to cooperate with each other, and it is also beneficial to improve the chemical stability of the glass powder.

[0096] According to the comparison of Comparative Examples 6-7 in Table 2 with Example 2, it can be obtained that when the D50 particle size of the modified zinc oxide is too small or too large, the glass powder cannot have a lower expansion coefficient and better water resistance and acid resistance. Therefore, only by using modified zinc oxide in a specific particle size range in the present invention can the chemical stability of the glass be better improved while further reducing the expansion coefficient of the glass, promoting the glass powder system to have good mechanical strength and thermal shock resistance, and enhancing the flexural strength of the glass powder.

[0097] According to Table 2, by comparing Comparative Examples 8-9 with Example 2, it can be found that in Comparative Example 8, an equal mass of magnesium oxide is used to replace calcium oxide, and in Comparative Example 9, an equal mass of bismuth oxide is used to replace boron oxide. The chemical stability and expansion coefficient of the glass powder in Comparative Examples 8-9 are not as good as those in Example 2, which shows that the present invention cannot achieve the effect of the present invention by using any substance in combination with silicon dioxide, aluminum oxide, zinc oxide, and alkali metal oxides.

[0098] According to the comparison between Examples 5-8 and Example 2 in Table 1, it can be seen that as the mass ratio of sodium oxide to potassium oxide increases, the expansion coefficient of the glass powder first decreases and then increases, and the flexural strength of the glass powder first increases and then decreases, indicating that when the mass ratio of sodium oxide to potassium oxide is controlled within a certain range ((3-5): 1), not only the expansion coefficient of the glass powder can be further reduced, but also the mechanical properties of the glass powder can be further improved.

[0099] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A lead-free glass powder, characterized in that: It is composed of the following components in parts by mass: 45-55 parts of boron oxide; 12-18 parts of silicon dioxide; 14-16 parts of aluminum oxide; 5-10 parts of modified zinc oxide; 6-10 parts of calcium oxide; 3-6 parts of alkali metal oxide; the D50 particle size of the modified zinc oxide is 20-50 nm; the modified zinc oxide is composed of Ti3C2T x The zinc oxide is obtained by coating and modifying the zinc oxide with nanosheets. The preparation method of the modified zinc oxide comprises the following steps: First, zinc oxide powder is prepared into a zinc oxide solution with a mass concentration of 3-6%, and then added into the Ti3C2Tx nanosheets and mixed evenly. After drying, the modified zinc oxide is prepared. x The mass ratio of the nanosheets is 1:

2.

2. The lead-free glass powder according to claim 1, characterized in that The alkali metal oxide is at least one of sodium oxide, lithium oxide and potassium oxide.

3. The lead-free glass powder according to claim 2, characterized in that: The alkali metal oxide is a mixture of sodium oxide and potassium oxide, and the mass ratio of the sodium oxide to potassium oxide is (3-5):

1.

4. The lead-free glass powder according to claim 3, characterized in that: The mass ratio of the sodium oxide to the potassium oxide is 4:

1.

5. The lead-free glass powder according to claim 1, wherein: The oil absorption of the glass powder is 15-20 g / 100g.

6. The method for preparing the lead-free glass powder according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Mix all components evenly to obtain a mixture; (2) The mixture is then heated and kept warm to obtain glass liquid, and the glass liquid is then poured into cold water for quenching to obtain glass particles; (3) Finally, the glass particles are ground into glass powder.

7. The method for preparing lead-free glass powder according to claim 6, characterized in that: In the step (2), the temperature of the mixed material during heating is 700-850° C., and the insulation time is 1-2 hours.

8. Use of the lead-free glass powder according to any one of claims 1 to 5 in semiconductors.